2018
DOI: 10.18438/eblip29404
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy Skills of First-Year Library and Information Science Graduate Students: An Exploratory Study

Abstract: Abstract Objective – This cross-sectional, descriptive study seeks to address a gap in knowledge of both information literacy (IL) self-efficacy and IL skills of students entering Louisiana State University’s Master of Library and Information Science (MLIS) program. Methods – An online survey testing both IL self-efficacy and skills was administered through Qualtrics. The online survey instrument used items from existing instruments (Beile, 2007; Michalak & Rysavy, 2016) and was distributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…In comparison to text analysis, surveys appear to be a more direct way to approach people's information science identity. Surveys of LIS students have been employed to approach or measure a range of areas, including specific aspects of students' skills, their professional skills and entrepreneurial aspirations (Ekpenyong & Gopeh, 2019), their information literacy (Hebert, 2018), visual literacy (Beaudoin, 2016), ICT skills (Hossain & Sormunen, 2019), or use of citation tools (Madhusudan, 2016). It seems that in these studies the use of surveys, despite that they could reach the target of study directly, may be very constrained in their capacity to deal with the complicated and intangible issue of identity.…”
Section: Related Workmentioning
confidence: 99%
“…In comparison to text analysis, surveys appear to be a more direct way to approach people's information science identity. Surveys of LIS students have been employed to approach or measure a range of areas, including specific aspects of students' skills, their professional skills and entrepreneurial aspirations (Ekpenyong & Gopeh, 2019), their information literacy (Hebert, 2018), visual literacy (Beaudoin, 2016), ICT skills (Hossain & Sormunen, 2019), or use of citation tools (Madhusudan, 2016). It seems that in these studies the use of surveys, despite that they could reach the target of study directly, may be very constrained in their capacity to deal with the complicated and intangible issue of identity.…”
Section: Related Workmentioning
confidence: 99%
“…Pour leur part, Hsin et al (2016) ont démontré que les doctorants moins expérimentés réalisaient davantage des recherches d'information en surface, c'est-à-dire centrées sur les meilleurs résultats de requêtes offerts par les moteurs de recherche, que leurs pairs plus expérimentés, soulignant du même coup l'importance de la formation à la recherche d'information pour ces étudiants. À ces nombreuses lacunes qui semblent perdurer, ajoutons que la littérature relève une tendance chez plusieurs des étudiants aux cycles supérieurs à surestimer leurs compétences en recherche d'information (Delaney et Bates, 2018;Hebert, 2018;Michalak et al, 2017;Robertson et Felicilda-Reynaldo, 2015;Spezi, 2016). En somme, si la recherche d'information représente la base de toute recherche menée par un étudiant de 2 e ou de 3 e cycle universitaire, il s'avère qu'elle n'est pas toujours bien maîtrisée.…”
Section: Contexteunclassified
“…Les autres se perçoivent comme étant soit avancés ou experts (29,6 %), soit débutants (19,6 %). D'une part, les étudiants aux cycles supérieurs en éducation semblent globalement démontrer une certaine humilité dans leur autoévaluation, ce qui ne semble pas être le cas chez d'autres collègues davantage enclins à surestimer leurs compétences en recherche d'information (Delaney et Bates, 2018;Hebert, 2018;Michalak et al, 2017;Robertson et Felicilda-Reynaldo, 2015;Spezi, 2016). Il serait intéressant de vérifier si des facteurs tels que leur domaine d'études (sciences de l'éducation) sont en jeu.…”
Section: Niveau D'expertise Par Rapport à L'utilisation Des Bases De unclassified
“…It is also witnessed that most of the studies concentrate on students, researchers and faculty members’ literacy skills, and lacks detailed studies on librarians’ skills with user community (Hebert, 2018). Moreover, no detailed studies on library professionals’ essentials skills are found in this region.…”
Section: Introductionmentioning
confidence: 99%